2016
DOI: 10.1101/042580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining multiple tools outperforms individual methods in gene set enrichment analyses

Abstract: Motivation: Gene set enrichment (GSE) analysis allows researchers to efficiently extract biological insight from long lists of differentially expressed genes by interrogating them at a systems level. In recent years, there has been a proliferation of GSE analysis methods and hence it has become increasingly difficult for researchers to select an optimal GSE tool based on their particular dataset. Moreover, the majority of GSE analysis methods do not allow researchers to simultaneously compare gene set level re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 50 publications
(50 reference statements)
0
45
0
Order By: Relevance
“…Spearman and Pearson correlations were computed for the top 15 cluster marker genes. Gene Set Enrichment Analysis(GSEA) was performed on the top 20 cluster marker genes using the R package EGSEA 34 with the KEGG pathway gene sets. SingleR 35 was used to annotate cell types based on correlation profiles with bulk RNA-seq from 36 .…”
Section: Comparative Analysis Of the 10x Genomics E18 Mouse Datasetmentioning
confidence: 99%
“…Spearman and Pearson correlations were computed for the top 15 cluster marker genes. Gene Set Enrichment Analysis(GSEA) was performed on the top 20 cluster marker genes using the R package EGSEA 34 with the KEGG pathway gene sets. SingleR 35 was used to annotate cell types based on correlation profiles with bulk RNA-seq from 36 .…”
Section: Comparative Analysis Of the 10x Genomics E18 Mouse Datasetmentioning
confidence: 99%
“…p-value ≤ 0.05, Table S1). Gene set testing using the Ensemble Of Gene Set Enrichment Analyses (EGSEA) method (Alhamdoosh et al, 2017) (Methods) showed gene sets directly associated with STAT3 signaling to be downregulated ( Figure S1A-B, Table S1).…”
Section: Low Stat3 Expression In Primary Pca Is Associated With Incrementioning
confidence: 99%
“…For gene set testing of transcriptomic and proteomic data, the Ensemble Of Gene Set Enrichment Analyses (EGSEA) R package v.1.10.1 (Alhamdoosh et al, 2017), was used. EGSEA allows to use results from up to twelve Gene Set Enrichment (GSE)-algorithms, covering competitive and self-contained methods (Goeman and Bühlmann, 2007), to calculate collective gene set scores.…”
Section: Gene Set Testingmentioning
confidence: 99%
“…7), in which subclone 4 is an unobserved genome inferred by TED. For SNVs and CNAs on each evolution step, we selected the mutations in the Coding DNA Sequence (CDS), which were labeled as CDS-SNVs and CDS-CNAs, respectively, and then used the Bioconductor package EGSEA 35 to carry out Gene Set Enrichment Analyses (GSEA) for the genes that harbored these mutations. GSEA was done separately for the genes with CDS-SNVs and for the genes with CDS-CNAs.…”
Section: Analysis Results Of Bulk Sample Subclones Of Breast Invasivementioning
confidence: 99%